RELASI KEKUASAAN DALAM PEMBUATAN PASPOR (Analisis Indeks Kepuasan Masyarakat di Kantor Imigrasi Kelas I Non Tempat Pemeriksaan Imigrasi Depok) - Rasya Alferina Hasna Dewi (2023)
This study aims to find out more in depth about the process of power relations in making passports that occur in the analysis of the community satisfaction index at Class I Immigration Offices Non Immigration Checkpoints Depok by using the theory of Service Quality Dimensions of Parasuraman, Berry & Zethaml, which emphasizes tangible aspects (Direct Evidence ), Reliability, Responsiveness, Assurance, and Empathy and uses Michel Foucault's Power Relations theory. The method used is descriptive qualitative using primary data sources and secondary data sources. Data collection techniques were carried out by observation, interviews and documentation. In this study the analysis technique used was data reduction, data presentation, and drawing conclusions. The final results of this study indicate that there is a relationship between immigration officials and service users that occurs in making passports which are considered to have deviated from the policy provisions stated in the legal umbrella and decreasing public satisfaction in the quality of service for making passports at the Immigration Office Class I Non TPI Depok. So the conclusion is that there is a power relationship in making passports (analysis of the public satisfaction index at the Immigration Office Class I Non Depok Immigration Checkpoints) Keywords: Service Quality, Passport Service, Power of Attorney Relations